Frontiers of diversity : explorations in contemporary pluralism - Plaw, Avery (Rodopi, 2005)
Frontiers of Diversity critically examines the explanatory and normative power of pluralism in contemporary philosophy, politics, economics and culture. Based on the papers presented at the "First Global Conference on Critical Issues in Pluralism" at Mansfield College, Oxford, it brings together for the first time essays examining pluralism's impact, both positive and negative, in each of these critical domains. These essays exhibit something of the fertility of the concept of pluralism, not only across the spectrum of fields, but at all levels of analysis, from individual to social to nationa.
Keywords: Cultural pluralism.; Globalization.; Diversité culturelle.; Mondialisation.; globalism.; SOCIAL SCIENCE -- Discrimination & Race Relations.; Cultural pluralism; Globalization; Pluralismus